Memoria, análisis y propuestas. II Encuentro del Mercosur ampliado. Máquinas y herramientas para la agricultura familiar: tecnologías apropiadas para la agricultura familiar - Tutuy, Manuel Roque (Comp.) (2012)
The development of Family Farming requires, among other things, the provision of appropriate technologies—including machinery and tools—that facilitate family work and contribute to the implementation of production, processing, and value-added processes with efficient use of energy, preferably renewable. In the region, there is a sector of companies, mostly micro-SMEs, that with great entrepreneurial spirit and effort are developing, manufacturing, and offering machinery and tools for Family Farming. State agencies and organizations in the sector have identified the need to contribute to strengthening this sector due to its strategic importance in the pursuit of more inclusive socio-productive development. This publication provides a clear demonstration of a process of coordination among various institutions involved in rural development and family farming. This process began with the first meeting in the province of Corrientes in 2010 and has been consolidated with the participation of numerous public and private organizations in the planning, design, and organization of this successful second meeting of the Expanded MERCOSUR. Machinery and Tools for Family Farming.